Capability of guideline-conform remote atrial high rate episode monitoring with a single-chamber implantable defibrillator with atrial sensing. (19th May 2022) - Maglia, G; Hindricks, G; Theuns, DA; Bar-Lev, D; Anguera, I; Ayala Paredes, FA; Arnold, M; Geller, JC; Merkely, B; Dyrda, KM; Perings, C; Ploux, S; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Private company. Main funding source(s): BIOTRONIK, Berlin, Germany Introduction: Device-detected atrial high-rate episodes (AHRE) and their burden progression are associated with an increased risk for thromboembolic events in correlation with CHA2DS2-VASc score and AHRE burden. To allow timely initiation of anticoagulation therapy for the prevention of stroke, the European guidelines on atrial fibrillation (AF) recommend the monitoring of AHRE progression along pre-specified strata (6min…<1h, 1h…<24, ≥24h). We sought to assess the capability of a single-lead implantable cardioverter defibrillator (ICD), that is equipped with an atrial dipole for atrial sensing, to remotely detect and monitor AHRE burden progression in patients with standard indication to single-chamber ICD. Methods: From the MATRIX (Management and Detection of Atrial Tachyarrhythmias in Patients Implanted With BIOTRONIK DX Systems) registry, we analyzed remotely transmitted, and electrogram (IEGM) AHREs in a subset of patients with remote transmissions and without history of long-standing AF at baseline. For each patient, we selected the first occurring episode per duration stratum and the first subsequent occurrence when progressing to a stratum of any longer duration. After episode adjudication by an independent electrophysiologist, we assessed the classification performance of the device (positive predictive value [PPV]) and analyzed AHRE onset and progression pathways. Results: Of the MATRIX cohort, 1, 746 patients matched the inclusions criteria (see table for patient characteristics) and 1, 451 had no AF history. Of the 258 patients with AHREs (14.8%), 450 out of 465 evaluated episodes were correctly classified as AHRE. Reasons for misclassification were artifact (13) and R-wave oversensing (2). PPV was 96.8% (95% confidence interval 94.7%-98.2%). Grouped by stratum, PPV was 93.9%, 99.5% and 100% for 6min…<1h, 1h…<24 and ≥24h, respectively. Ninety six of 240 patients (40.0%) with a first episode according to the pre-specified strata were progressing to a stratum of longer duration and 9 patients (3.8%) had further progression (see Figure). In 119 out of 1, 451 patients without AF history (8.2%), the device detected AHRE and 81 of them (4.6% of analysis set) had a mid to high risk for stroke and were not on anticoagulation therapy. In 121 out of 295 patients with known history of paroxysmal and persistent AF (41.0%), the arrhythmia was confirmed by the device. Discussion and Conclusion: The single-chamber ICD with atrial sensing capabilities correctly classified ≈97% of all adjudicated AHREs ≥6min. About 7% of patients had device-detected AHRE onset and/or progression and a mid to high stroke risk. These patients would potentially benefit the most from a guideline-conform AF monitoring strategy to timely initiate anticoagulation medication for stroke prevention.